LINGUISTIC INTERPRETATION OF THE DIFFERENCE OF THE HARAKAT OF LETTERS IN THE RECITATION OF AL-QIRA'AT AL-'ASYR - Amin Kahila, Muhammad ad-Dasuki; Nasir, Husain; Sabry, Muhammad Sadik; Malik, Firdaus; Has, Muhammad Hadsin (Living Islam: Journal of Islamic Discourses, 2024)
In the science of Qiraat, the problem of vowel reading on letters and words in the Qur'an is still much that has not been revealed, both from the aspect of classical and modern scholarly opinions. This study aims to describe and introduce several rules about the process of occurrence of vowel a/i/u in certain words and verses, which are caused by the presence of letters, hamzah, sukun, and ishmam, including exploring new ways of analyzing the phonology of modern Arabic vowels based on standard generative theory. This research is literature research. Primary data sources were obtained by al-Našr fi al-Qirā'at al-Islāmiyyah, and several verses of the Qur'an for comparison. Secondary data sources are literature, both in the form of books, journals, and research results related to phonology. Data collection is carried out by documentation techniques, listening, and recording. Data analysis techniques use open coding, then analyzed descriptively using grounded theory. This study informs about the rule that the variety of vowel punctuation on some verbs in the Qur'an will change according to the readings attributed to the ten Qira'at. The Vowel sign emphasizes the reading of dammah/kasrah). The emphasis mark on nouns requires the insertion of dammah while on verbs and insertion of kasrah. The round distinguishing mark (sifr) is important in turning kasrah into dammah. Both Kasrah and dammah have the property of 'Al, but some of them are distinguished by round marks on dammah and square marks on kasrah. The Vowel sign for classical scholars indicates that the kasrah from the letter "waw" in the verb "qul" moved to the letter "qaf" after hadzf dammah, then "waw" changed to "ya" to correspond to the kasrah in front of it. Modern linguists believe that the dammah of the letter "qaf" can be changed to Kasrah and then "waw" removed, so that the existence of the two kasrahs is merged and becomes a long shaddah. The differences and changes in vowels in phonetics cannot be separated from the debate that exists between classical and modern scholars. This indicates that the problem of qira'at is closely related to diacritical marks that are icons of producing sounds with various characters. This research has implications that having to study Qur'anic verses from a Vowel aspect will require us to see how scholars used to read so that the sounds produced are not only one variant but have a variety of very detailed and interesting reasons to be studied based on modern linguistic theory. Keywords: Vowel; linguistic interpretation; recitation, Qira’at Ten   Dalam ilmu Qiraat, persoalan bacaan vokal pada huruf dan kata-kata dalam al-Qur’an masih banyak yang belum diungkap, baik dari aspek pendapat ulama klasik maupun modern. Penelitian ini bertujuan untuk mendeskripsikan  dan mengenalkan  beberapa kaidah tentang proses terjadinya vokal a/i/u pada kata dan ayat tertentu, yang disebakan oleh adanya huruf, hamzah,  sukun dan isymam, termasuk  mengeksplorasi cara-cara baru dalam menganalisis fonologi vokal bahasa Arab modern berdasarkan teori generatif standar. Penelitian ini merupakan penelitian kepustakaan. Sumber data primer diperoleh al-Našr fi al-Qirā'at al-Islāmiyyah, dan beberapa ayat al-Qur’an sebagai bandingannya. Sumber data sekunder adalah literatur, baik berupa buku-buku, jurnal dan hasil-hasil penelitian yang berkaitan dengan fonologi. Pengumpulan data dilakukan dengan teknik dokumentasi, simak dan catat. Teknik analisis data menggunakan  pengkodean terbuka, lalu dianalisis secara deskriptif menggunakan grounded theory. Penelitian ini menginformasikan tentang kaidah bahwa ragam tanda baca vowel pada beberapa kata kerja dalam al-Qur’an akan berubah sesuai dengan bacaan yang dinisbatkan kepada sepuluh Qira’at. Tanda Vowel menekankan pada bacaan dammah/kasrah). Tanda penekanan pada kata benda mengharuskan penyisipan dammah sedangkan pada kata kerja dan penyisipan kasrah. Tanda pembeda bulat (sifr)penting dalam mengubah kasrah menjadi dammah. Baik Kasrah maupun dammah sama-sama memiliki sifat ‘Al, namun beberapa di antaranya dibedakan dengan tanda bulat pada dammah dan tanda persegi  pada kasrah. Tanda Vowel bagi ulama klasik  mengiformasikan bahwa kasrah dari huruf “waw” pada kata kerja “qul” berpindah ke huruf “qaf” setelah terjadi hadzf dammah, kemudian “waw” berubah menjadi “ya” agar sesuai dengan kasrah di depannya. Sedangkan bagi para linguis modern meyakini bahwa dammah dari huruf “qaf” dapat berubah menjadi Kasrah dan kemudian “waw” dihapus, sehingga keberadaan kedua kasrah tersebut digabung dan menjadi shaddah yang panjang. Perbedaan dan perubahan Vowel dalam ilmu fonetik tidak lepas dari perdebatan yang pajang antara ulama klasik dan modern. Hal ini mengindikasikan bahwa masalah qira’at sangat berkaitan dengan tanda diakritik yang menjadi icon penghasil bunyi dengan aksara yang  beragam. Penelitian ini berimplikasi pada  keharusan  mempelajari ayat-ayat Al-Qur’an dari aspek Vowel akan mengharuskan kita untuk melihat kmbali seperti apa para ulama dulu membaca, sehingga bunyi-bunyi yang dihasilkan tidak hanya satu varian, namun memiliki ragam alasan yang sangat detail dan menarik untuk dipelajari berdasarkan teori linguistik modern. Kata kunci: Linguistik interpretasi:  Suara, Vokal, Qiraat 10 mutawatir